Business Activity and Its Impact on Crime - Jozef KUBAS; Stanislava STRELCOVA; Viktor SOLTES (Communications of International Proceedings, 2021)
Quality of life is affected by a number of aspects and with the context of the current situation, safety is one of the most important. For safety Each individual is influenced by a number of factors, hence the perception of safety for each individual. One of the objective indicators of the security situation it is precisely crime that negatively affects a person's safety and at the same time his quality of life. To improve the security situation of people in terms of crime is it is necessary to know the risks that flow from it. In the article, we focused on the business environment in Slovakia. We analyzed the development of business activity over a period of time. With the help of comparison, we pointed out whether there is any connection with the development of crime and the development of business activity.
Keywords: Security; Entrepreneurship; Economic Growth; Crime.